2002
DOI: 10.1142/s0192415x02000260
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine Induces Neurite Outgrowth in PC12 Mutant Cells Incapable of Differentiation

Abstract: During continuous culture of neural PC12 cells, we obtained a drug-hypersensitive PC12 mutant cell that showed high stimulation of neurite outgrowth by various drugs. When several Chinese medicines such as shu-jing-huo-xie-tang and Wu-Ling-San were provided to these PC12 mutant cells, the frequency of nerve growth factor (NGF)-induced neurite outgrowth increased approximately 30-fold compared to NGF alone. Neurite outgrowth induced by NGF in PC12 cells is accompanied by sustained activation of mitogen-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Traditionally, DSS was used to relieve menorrhalgia and other abdominal pains of women [12, 13]. The therapeutic effect of DSS on Alzheimer's disease was also reported [14, 15]. Beneficial effect of DSS on AGEs-mediated renal injury in diabetic rats has been clarified in the present study.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Traditionally, DSS was used to relieve menorrhalgia and other abdominal pains of women [12, 13]. The therapeutic effect of DSS on Alzheimer's disease was also reported [14, 15]. Beneficial effect of DSS on AGEs-mediated renal injury in diabetic rats has been clarified in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…DSS has been used in China as a blood-activating and stasis-eliminating drug to treat gynecological disorders such as dysmenorrhea, amenorrhea, and infertility without observation of side effects for thousands of years [12, 13]. Recent studies show that it also possesses the capability of treating neural dysfunctions such as senile dementia, memory loss, and other cognitive disorders; thus the formula is used as a remedy for Alzheimer's disease in Japan [14, 15]. The amelioration of streptozotocin diabetes-induced renal damage by the herbal formula containing Poria cocos , R. Alismatis , and R. Atractylodis macrocephalae has been documented [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some other natural medicines can upregulate NGF in astrocytes (9,12). It has recently been suggested that some natural medicines are useful for the treatment of neurosis (7,9,19). Since none of the Trk high affinity receptors for NGF, BDNF and NT-3 are present in C2C12 cells (14,17), but are found on PC12D cells, we suggest that these neurotrophins could mediate the neurotrophic effects efficiently on the PC12D cells in the co-culture system.…”
Section: Discussionmentioning
confidence: 82%
“…The effectiveness of E11, E30, E38 and E73 on muscle and neuronal cells have been reported (4-6, 8, 11, 18). Some other natural medicines can upregulate NGF in astrocytes (9,12). It has recently been suggested that some natural medicines are useful for the treatment of neurosis (7,9,19).…”
Section: Discussionmentioning
confidence: 99%
“…[3132] Recent studies show that it also possesses the capability of treating neural dysfunctions such as senile dementia, memory loss, and other cognitive disorders; therefore, the formula is used as a remedy for Alzheimer's disease in Japan. [3334]…”
Section: Recent Findings From the Selected Traditional Chinese Medicimentioning
confidence: 99%